The Emotional and Personality-Related Career Decision-Making Difficulties Questionnaire—Validation of the Chinese Version. (May 2016) - Hou, Zhi-Jin; Li, Xu; Liu, Yi-Ling; Gati, Itamar
The purpose of the present study was to examine the internal consistency and test–retest reliability, the internal structure, and construct validity of the Chinese version of the Emotional and Personality-Related Career Difficulties questionnaire ( EPCD ). Based on a sample of 540 Chinese university students, high-reliability coefficients for the overall scale (α = .93), the three clusters (.78, .85, and .93), and adequate reliability for its 11 difficulty categories (range from .64 to .85) were observed. The 2-week test–retest reliabilities of the overall scale, three clusters, and 11 difficulty categories were also adequate (ranging from .61 to .94). Confirmatory factor analysis of the original theoretical model (11 difficulty categories loaded on three major clusters and then one general factor) demonstrated acceptable model fit after deleting three small-loading items. The pattern of associations between the clusters of the EPCD and the Trait Anxiety Scale, the Career Decision Scale, and the Vocational Identity Scale supported its construct validity. The discussion of the use of EPCD in China and suggestions for future research are proposed.